Семантика Х5 в українській поезії - Гаврилюк, Надія; Gavryliuk, Nadiya (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті йдеться про види семантичного ореолу ліричного п’ятистопного хорея в циклі М. Рильського «Голосіївська осінь» та поезії молодих українських авторів.The article highlights the kinds of semantic aureoles of trochee pentameter in the cycle by M. Rylsky «Golosіjivs’ka osin» and in the poetry of the young Ukrainian authors. In verses by M. Rylsky there is an elegiac clearness, while in the younger poets melancholy mood is stronger. Semantic aureoles of X5 are characterized by the following components: landscape autumn and landscape winter, night, road, memories / memory, loneliness, old age, death approaching, family love, love, creativity and progress. The rhythmic introductions are not directly related with semantic aureoles. Most often this relationship occurs, when attached to the identity introductions lexical and syntactic similarity, as in the poems of M. Rylsky «Lastіvky lіtayut’, bo lіtajetsya» and Lina Kostenko «Lastіvky tіkayut’ іz Jevropy».
Semantics of X5 in the Ukrainian poetry
Keywords: семантичний ореол; ліричний п’ятистопний хорей; дорога; любов; semantic aureoles; lyric trochee pentameter; road; love